Fabrication, structural characteristics, and influence of Bi3+ doping concentration on UV-vis spectra of Bi3+:SnO2 nanocomposite materials - Thi Thu Hien Le; Van Tuan Chu; Van Tuan Pham (Vietnam Journal of Science, Technology and Engineering, 2023)
The authors report the characteristics and optical properties of Bi3+-doped SnO2 quantum dots prepared by sol-gel and hydrothermal methods. The structure and morphology of the materials as a function of doping concentration were studied and analysed by X-ray diffraction (XRD) and scanning electron microscope (SEM). The structure of the material was assigned to the tetragonal crystal structures of the SnO2 rutile phase, reported in JCPDS Card No. 41-1445. With the increase of Bi3+ doping, the crystallinity of Bi-doped SnO2 worsened. The average sizes of the SnO2 nanocrystals were within 3-8 nm. The effect of Bi3+ ion concentration on the absorbance properties of the materials was investigated by UV-Vis absorption spectra. The absorbance decreased with increasing the concentration of Bi3+ dopant in the SnO2 lattice. The bandgap width decreased with Bi3+ dopant concentration. All Bi3+-doped SnO2 samples presented an enlargement of the light absorption range due to a bandgap width decrease.